Novel compound heterozygous mutations in inositol polyphosphate phosphatase-like 1 in a family with severe opsismodysplasia. Issue 4 (October 2016) - Feist, Cori; Holden, Paul; Fitzgerald, Jamie
Abstract : This study aimed to identify the genetic basis of a severe skeletal lethal dysplasia. The main clinical features of two affected fetuses included short limbs with flared metaphyses, bowed radii, femora and tibiae, irregular ossification of hands and feet, and marked platyspondyly. Affected and nonaffected family members were subjected to whole-exome sequencing, followed by immunoblot analysis on amniocytes isolated from one of the affected individuals. Unique compound heterozygous variants in the inositol polyphosphate phosphatase-like 1 ( INPPL1 ) gene encoding the SHIP2 protein were identified in both affected individuals. One variant was inherited from each unaffected parent. Both allelic variants, c.(2327−1G>C);(1150_1151delGA), are predicted to result in premature stop codons leading to nonsense-mediated mRNA decay of the mutant alleles and no production of SHIP2. The absence of SHIP2 was confirmed by immunoblot analysis of proband amniocytes. This skeletal disorder is caused by the complete absence of the SHIP2 protein. INPPL1 mutations have been reported in opsismodysplasia, an autosomal recessive skeletal dysplasias with significant delayed bone formation. Our finding highlights the critical role that INPPL1 /SHIP2 plays in skeletal development.